Channeling of Carbon Flux Towards Carotenogenesis in Botryococcus braunii: A Media Engineering Perspective - Mariam, Iqra; Kareya, Mukul Suresh; Rehmanji, Mohammed; Nesamma, Asha Arumugam; Jutur, Pannaga Pavan (Frontiers in Microbiology, 2021)
Microalgae, due to their unique properties, gained attention for producing promising feedstocks having high content of proteins, antioxidants, carotenoids and terpenoids for applications in nutraceutical and pharmaceutical industries. Optimizing production of the high value renewables (HVRs) in microalgae requires an in-depth understanding of their functional relationship of the genes involved in these metabolic pathways. In the present study, bioinformatic tools were employed for characterization of the protein-encoding genes of methyl erythritol phosphate (MEP) pathway involved in carotenoid and squalene biosynthesis based upon their conserved motif/domain organization. Our analysis demonstrates nearly 200 putative genes showing a conservation pattern within divergent microalgal lineages. Further, phylogenomic study confirm the close evolutionary proximity among these microalgal strains in the carotenoid and squalene biosynthetic pathways. Further analysis employing STRING predicts interactions among two rate-limiting genes; i.e., phytoene synthase (PSY) and farnesyl diphosphate farnesyl synthase (FPPS), which are specifically involved in the synthesis of carotenoids and squalene. Experimentally, to understand the carbon flux of these rate-limiting genes involved in carotenogenesis, an industrial potential strain namely Botryococcus braunii was selected in this study for improved biomass productivity (i.e., 100 mg L-1 D-1) along with enhanced carotenoid content (0.18 % DCW) when subjected to carbon supplementation. In conclusion, our approach of media engineering demonstrates that the channelling of carbon flux favours carotenogenesis rather than squalene synthesis. Henceforth, employing omics perspectives will further provide us with new insights for engineering regulatory networks for enhanced production of high value carbon biorenewables without compromising growth.